TANGGUNG JAWAB KORPORASI DALAM KASUS KEBOCORAN DATA SERTA IMPLIKASINYA TERHADAP EKONOMI DIGITAL - Santos, Ricardo; Multiwijaya, Vientje Ratna (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: In today's digital era, the protection of personal data has become a crucial issue for companies operating in the technology and e-commerce sectors. The increasing reliance on information technology correlates with a higher risk of data breaches, which can harm individuals and damage corporate reputations. The data breach cases involving Tokopedia and Gojek highlight the serious consequences of inadequate data security systems, raising public doubts about these companies' ability to protect user information. These incidents underscore the importance of corporate criminal liability and the need for a thorough evaluation of existing regulations to ensure more effective consumer protection. This research employs a normative legal approach to analyze legal principles and the synchronization of laws, providing practical implications for the development of a more sustainable and equitable national legal framework. It is hoped that the findings will aid in formulating solutions to address future data breach challenges and strengthen the legal framework for consumer protection in Indonesia.